Nonlinear optical studies of phthalocyanines and triazatetrabenzcorroles in solution and in thin films - Mkhize, Nhlakanipho Colin (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
This work presents photophysical and nonlinear optical properties of a novel Cd 2,3-[octakis{4-tert-butylphenoxyphthalocyanine}] (CdOtBPPc) and compared with those of Pb 2,3-[octakis{4-tert-butylphenoxyphthalocyanine}] (PbOtBPPc). For both the CdOtBPPc and PbOtBPPc, third order imaginary susceptibility and second order hyperpolarizability values were found to be within the limit set for good optical limiters. The Pcs were embedded in poly (methyl methacrylate) (PMMA) and poly(bisphenol A carbonate) (PBC) as thin films. The optical limiting values of the Pcs once embedded in film were found to be greatly improved and the limiting intensity of each film was well below the maximum threshold. Both PbOtBPPc and CdOtBPPc showed better optical limiting when embedded in PBC compared to PMMA. CdOtBPPc shows better nonlinear optical behaviour than PbOtBPPc in solution and as thin films, even though the former is aggregated in solution. Novel phosphorus triazatetrabenzcorroles (TBC) tetrasubstituted at the Î±- and Î²- and octa substituted at the Î²- positions of the peripheral fused benzene rings with t-butylphenoxy substituents were prepared and characterized. The effects of the substituents and the missing aza-nitrogen on the electronic structures and optical spectroscopy are investigated with TD-DFT calculations and MCD spectroscopy. The optical limiting properties were investigated to examine whether the lower symmetry that results from the direct pyrrole-pyrrole bond and hence the permanent dipole moment that is introduced result in higher safety thresholds, relative to the values that have been reported for phthalocyanines. The suitability of the compounds for singlet oxygen applications has also been examined. Novel phosphorus phthalocyanines, analogous to the triazatetrabenzcorroles were also investigated. Due to their high photodegradation quantum yield however, only the fluorescence quantum yields and lifetimes were able to be determined.
Keywords: Phthalocyanines; Thin films; Nonlinear optics; Phosphorus